The Regulatory Network of Cyclic GMP-AMP Synthase-Stimulator of Interferon Genes Pathway in Viral Evasion - Hu, Tongyu; Pan, Mingyu; Yin, Yue; Wang, Chen; Cui, Ye; Wang, Quanyi (Frontiers in Microbiology, 2021)
Virus infection has been consistently threatening public health. The cyclic GMP-AMP synthase (cGAS)-Stimulator of Interferon Genes (STING) pathway is a critical defender to sense various pathogens and trigger innate immunity of mammalian cells. cGAS recognizes the pathogenic DNA in the cytosol and then synthesizes 2′3′-cyclic GMP-AMP (2′3′cGAMP). As the second messenger, cGAMP activates STING and induces the following cascade to produce type I interferon (IFN-I) to protect against infections. However, viruses have evolved numerous strategies to hinder the cGAS-STING signal transduction, promoting their immune evasion. Here we outline the current status of the viral evasion mechanism underlying the regulation of the cGAS-STING pathway, focusing on how post-transcriptional modifications, viral proteins, and non-coding RNAs involve innate immunity during viral infection, attempting to inspire new targets discovery and uncover potential clinical antiviral treatments.